Keterampilan Kerja Lulusan Pendidikan Kejuruan dan Relevansi Kompetensi Melalui Praktik Industri di Dunia Kerja - Mahendra, Bayu Zulfa; Oktaviani, Silvia; Gusti, Muhamad Habil Cahaya; Wardoyo, Siswo (Universitas Lampung, 2024)
Vocational education plays an important role in preparing graduates who are in line with industry needs, but there is a gap between the competencies of graduates and the demands of the world of work, leading to high unemployment rates of vocational graduates. This study explores the employability skills of vocational education graduates and the relevance of their competencies through industrial practice with a qualitative approach and literature study. Of the six articles analyzed, five used qualitative methods, one quantitative, and none applied R&D methods, thus opening up opportunities for further exploration. The majority of the studies examined students and industry, with interviews and observation as the main instruments. The findings suggest that employability skills research in vocational education tends to focus on qualitative approaches and the relationship between the education sector and industry. This research is expected to provide insights for curriculum development that is more in line with the needs of the world of work.Kata kunci: Industri, Kerja, Keterampilan, Pendidikan, Praktik